Pengaruh Variasi Suhu Sebelum dan Setelah Penyimpanan terhadap Stabilitas Fisik dan Kontaminasi Bakteri Suspensi Antasida Generik - Rica Laily Istighfarin; Siti Nur Azizah; Asa Falahi; Amaliyah Nurul Hidayah (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
The purpose of this study was to determine the effect of temperature variations before and after storage on physical stability and bacterial contamination of the antacid suspension. The samples in this study were generic antacid suspensions with variations in storage temperature stored at 15-30°C (room), 2-8°C (cold), and 30-40°C (warm). Physical evaluations were carried out in the form of organoleptic tests, pH tests, viscosity tests and there was a bacterial contamination test. The results of the organoleptic test showed that the generic antacid suspension before and after storage had no change in smell, color and taste. The pH test has a stable pH and meets the requirements, namely pH between 7.3 and 8.5, the statistical test results obtained were 0.589> 0.05, which means that the pH before and after storage there was no significant difference. The viscosity test met the requirements, namely viscosity from 0.37 to 3.9 dpas. statistical test results obtained 0.023 <0.05, which means that the viscosity before and after storage there was a significant difference. The results of the Total Plate Number test before storage there was no contamination with ALTB values, namely 1.3x101 colonies/ml, 1,3x101 colonies/ml, and 1x101 colonies/ml, based on The International Pharmacopeia-7th edition the requirement for suspension bacterial contamination ≤ 1x102 colonies/ml, the result showed that contamination happened in all samples after storage. It can be concluded that bacterial contaminatios occured in all samples with temperature variations before and after storage but not affected on physical stability of antacid suspension.